2023
DOI: 10.3390/nu15020276
|View full text |Cite
|
Sign up to set email alerts
|

Stance4Health Nutritional APP: A Path to Personalized Smart Nutrition

Abstract: Access to good nutritional health is one of the principal objectives of current society. Several e-services offer dietary advice. However, multifactorial and more individualized nutritional recommendations should be developed to recommend healthy menus according to the specific user’s needs. In this article, we present and validate a personalized nutrition system based on an application (APP) for smart devices with the capacity to offer an adaptable menu to the user. The APP was developed following a structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The PROTEIN project emerges as an effort from experts in the field to provide advice based on sound science, in a world were m-Health (mobile health) applications providing nutritional and fitness guidance are increasing in popularity ( 335 ). The Stance4Health (Smart Technologies for personAlised Nutrition and Consumer Engagement) Nutritional APP is also a project funded by the European Union, through the Horizon 2020 research and innovation program, with the objective to develop mobile technologies for personalized nutrition ( 337 , 338 ). The aim of the APP is to generate menus tailored to the user’s characteristics, including a gut microbiota module based on 16S rRNA sequencing from fecal samples.…”
Section: Personal Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PROTEIN project emerges as an effort from experts in the field to provide advice based on sound science, in a world were m-Health (mobile health) applications providing nutritional and fitness guidance are increasing in popularity ( 335 ). The Stance4Health (Smart Technologies for personAlised Nutrition and Consumer Engagement) Nutritional APP is also a project funded by the European Union, through the Horizon 2020 research and innovation program, with the objective to develop mobile technologies for personalized nutrition ( 337 , 338 ). The aim of the APP is to generate menus tailored to the user’s characteristics, including a gut microbiota module based on 16S rRNA sequencing from fecal samples.…”
Section: Personal Genomicsmentioning
confidence: 99%
“…The aim of the APP is to generate menus tailored to the user’s characteristics, including a gut microbiota module based on 16S rRNA sequencing from fecal samples. A preliminary study showed promising results, providing nutritional education and useful interventions advice that could have a positive impact if used for a prolonged period of time ( 337 ). The mobile application Zoe has also recently emerged and gained popularity, providing personalized nutritional advice based on blood fat and sugar, and gut microbiome testing ( 339 ).…”
Section: Personal Genomicsmentioning
confidence: 99%
“…In breast cancer patients, a mobile app to promote physical activity showed good acceptability and feasibility, and the intervention promoted positive behaviours [ 145 ]. The Stance4Health Nutritional app integrates data on dietary preferences, nutritional requirements, body weight and physical activity with 16rRNA gene sequencing for gut microbiota data to provide personalised recommendations based on metabolic interactions between foods and the microbiota species [ 146 ]. Perhaps the most comprehensive app developed to date is the Zoe app, which identified predictors of individual responses to meals using genetic, metabolic, microbiome and meal composition data [ 46 ].…”
Section: Translation Of Nutrigenomic Research For Personalised and Pr...mentioning
confidence: 99%